The supply and demand balance of recyclable textiles in the Nordic countries - Dukovska-Popovska Iskra; Kjellsdotter Ivert Linea; Jonsdottir Hafdís; Dreyer Heidi Carin; Kaipia Riikka (Elsevier (Commercial Publisher), 2025)
The textile industry is on its early steps towards circular economy. Being a highly resource-intensive and waste-generating industry, it is essential to embrace fiber-to-fiber recycling in addressing the increasing textile waste problem. Several innovative initiatives are happening within this area, not least in the Nordic countries, where automated sorting and fiber-to-fiber recycling technologies and capacities are developing. These large investments require economy of scale; however, this is challenged by the fractioned supply due to the specific fiber requirements of the recycling facilities. To ensure economy of scale and support strategic planning, it is important to investigate the balance of the demand of those capacities with the supply of recyclables generated in the region. Local and regional perspectives are needed in order to avoid unnecessary transportation of low value materials. Based on a synthetises of existing textile flow studies and interviews with relevant actors in four Nordic countries, this study investigates the balance between the supply of recyclable textiles and the sorting and recycling capacity. This is accomplished by estimating the volumes of recyclables and their fiber composition (based on developed weighting average method) and comparing these with the current and upcoming capacities in each country and in the Nordics as a whole. The findings indicate that the upcoming automatic sorting and recycling capacity will be sufficient to deal with the total recyclable fraction in the Nordic region, except for some of the synthetic fibers. However, there are imbalances between supply and demand within individual countries, highlighting opportunities for collaboration.